Impact of triglyceride levels on plaque characteristics in patients with coronary artery disease. (1st February 2022) - Asakura, Kiyoshi; Minami, Yoshiyasu; Kinoshita, Daisuke; Katamine, Masahiro; Kato, Ayami; Katsura, Aritomo; Sato, Toshimitsu; Muramatsu, Yusuke; Hashimoto, Takuya; Kameda, Ryo; Meguro, Kentaro; Shimohama, Takao; et al.
Abstract: Background: High triglyceride (TG) levels have been demonstrated to be a risk factor for coronary artery disease. This study aimed to clarify the impact of TG levels on the characteristics of coronary plaques. Methods: A total of 850 consecutive patients who underwent optical coherence tomography (OCT) imaging of the culprit lesion were included. The morphologies of culprit plaques were compared between the higher TG group (nonfasting TG levels ≥150 mg/dL, n  = 337) and the lower TG group (nonfasting TG <150 mg/dL, n  = 513). Results: The prevalence of lipid-rich plaques (43% vs. 33%, p  = 0.005), thin-cap fibroatheromas (TCFAs) (24% vs. 17%, p  = 0.015) and macrophages (40% vs. 31%, p  = 0.006) was significantly higher in the higher TG group than in the lower TG group. In addition to a high low-density lipoprotein cholesterol (LDL-C) level (≥140 mg/dL), high TGs (≥150 mg/dL) were identified as an independent factor for the presence of TCFAs (odds ratio 1.465, 95% confidence interval 1.004–2.137, p  = 0.048). Among patients with lower LDL-C levels (<100 mg/dL), the prevalence of macrophages (38% vs. 26%, p  = 0.007) and layered plaques (48% vs. 38%, p  = 0.019) was significantly higher in the higher TG group than in the lower TG group. Conclusions: Higher TG levels were associated with a higher prevalence of TCFAs in culprit coronary lesions. The prevalence of macrophages and layered plaques was more frequently observed in patients with higher TGs than those with lower TGs among patients with LDL-C < 100 mg/dL. Graphical abstract: Characteristics of culprit plaque in patients with coronary artery disease according to triglyceride levels. Unlabelled Image Highlights: Higher TG (≥150 mg/dL) is associated with more TCFAs in coronary lesions. Higher TG is associated with more lipid-rich plaques in patients with high LDL-C. Higher TG is related to more macrophages and layered plaques in low LDL-C patients. These results may explain the role of TGs in the development of coronary plaques.